ANALISIS INKLUSIVITAS RUANG TERBUKA PUBLIK UNTUK LANSIA DAN ANAK DI KAWASAN PERKOTAAN (STUDI KASUS: TAMAN KOTA DI MATARAM): An Analysis of the Inclusiveness of Public Open Spaces for the Elderly and Children in Urban Areas (Case Study: City Parks in Mataram) - Bagus Widhi Dharma S. (Yayasan Al-Amin Qalbu, 2026)
The objectives of this study are to: 1) Analyze the level of inclusivity of public open spaces—specifically city parks—in Mataram for the elderly and children. 2) Identify the factors influencing the inclusivity of city parks for the elderly and children. 3) Evaluate the conditions regarding accessibility, safety, comfort, and facilities in Mataram's city parks. 4) Formulate strategic recommendations for developing city parks that are more inclusive for the elderly and children in urban areas. This study employs a mixed-methods approach with a sequential explanatory design, combining quantitative and qualitative methods in sequence to gain a comprehensive understanding of the inclusivity levels of public open spaces for the elderly and children. The results indicate that the level of inclusivity in Mataram's city parks is quite good, with an average inclusivity index of 3.27 for both the elderly and children. The factors influencing this inclusivity include accessibility, safety, comfort, and the provision of inclusive facilities. Observations and index assessments regarding accessibility, safety, comfort, and facility completeness generally yielded scores between 3 and 4; thus, while conditions are already quite good, there remains room for further completion and improvement.